Penerapan Senam Yoga Terhadap Tekanan Darah Pada Penderita Hipertensi Di Kelurahan Jebres Surakarta - Endyta Youlastri Ayuningtyas; Maryatun Maryatun (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hypertension is one of the issues challenging the medical community today. In Indonesia, the prevalence of hypertension is 34.1%, or 63,309,630 million individuals. Since hypertension is frequently referred to as the